Psychological Impact of Breast Cancer Diagnosis and Patient Coping Strategies: A Literature Review - Myint, Nyein Moh Moh; Martawinarti, Rts. Netisa; Nasution, Riska Amalya; Sari, Putri Irwanti; Sari, Lisa Anita; Oktaria, Rina; Mutmainnah, Muthia (Jurnal Ilmiah Ners Indonesia, 2025)
Breast cancer is the most commonly diagnosed cancer and leading cause of cancer-related mortality among women globally. Beyond its physical impact, it brings complex psychological consequences, including stress, depression, anxiety, and post-traumatic stress disorder (PTSD), which can affect treatment adherence and quality of life. This literature review aims to explore the psychological impact of breast cancer diagnosis and identify the coping strategies used by patients to manage their emotional burden. A literature review was conducted using databases such as PubMed, Scopus, DOAJ, and Google Scholar. Selected studies focused on psychological effects and coping mechanisms among breast cancer patients, including family and social support, cultural-religious factors, and psychological interventions. The findings show that emotional distress following a breast cancer diagnosis is influenced by cancer stage, treatment type, physical changes, support systems, and cultural belief. Adaptive coping strategies such as religious faith, emotional support, positive reframing, and acceptance promote psychological adjustment and treatment compliance. In contrast, maladaptive strategies like avoidance and denial worsen emotional outcomes. Breast cancer has a profound psychological impact requiring comprehensive mental health care. Integrating psychological and cultural-religious support into cancer treatment improves emotional well-being and clinical outcomes.